2016
DOI: 10.1186/s12889-016-3541-8
|View full text |Cite
|
Sign up to set email alerts
|

Rational use of antibiotics by community health workers and caregivers for children with suspected pneumonia in Zambia: a cross-sectional mixed methods study

Abstract: BackgroundAntibiotic resistance is an issue of growing global concern. One key strategy to minimise further development of resistance is the rational use of antibiotics, by providers and patients alike. Through integrated community case management (iCCM), children diagnosed with suspected pneumonia are treated with antibiotics; one component of an essential package to reduce child mortality and increase access to health care for remote populations. Through the use of clinical algorithms, supportive supervision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 29 publications
1
36
2
2
Order By: Relevance
“…All observational studies reported on the use of healthcare information during consultations, which is reported in table 3 for nine studies involving a survey and in table 4 for the five qualitative studies. The most mentioned information sources used during consultations were books,7 19–23 leaflets,20 guidelines,7 20 21 24–28 a flip chart and reporting form aid,29 and the internet 7 21 24 26 30 31. A survey conducted in Harare, Zimbabwe, in 2006 found that 28 out of 46 community pharmacists (61%) used the internet for practice and 23 (50%) mentioned using Google 24.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All observational studies reported on the use of healthcare information during consultations, which is reported in table 3 for nine studies involving a survey and in table 4 for the five qualitative studies. The most mentioned information sources used during consultations were books,7 19–23 leaflets,20 guidelines,7 20 21 24–28 a flip chart and reporting form aid,29 and the internet 7 21 24 26 30 31. A survey conducted in Harare, Zimbabwe, in 2006 found that 28 out of 46 community pharmacists (61%) used the internet for practice and 23 (50%) mentioned using Google 24.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent survey in Nigeria in 2016 found that 46 out of 115 community pharmacists (40%) searched the internet several times a day for drug information and only 8 (7%) never searched the internet 30. A study observing community health worker consultations with children who had suspected pneumonia in Zambia found low use of the flip chart and reporting form aid and suggested this might be because community health workers were confident in their recall of the diagnostic integrated community case management algorithm 29. Reasons for not using books were that it took too much time to use them,7 23 prescribers felt confident in their decisions, were too busy or felt ashamed to use it in front of patients 23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore SA needs to set up a more comprehensive training program because CMAM alone requires advanced skills of routine growth monitoring, administering antibiotics and RUTF (Puett et al, Puett, Sadler, et al, ). Intervention‐based CHWs in and Zambia have proven capable of administering appropriate amounts of antibiotics for SAM and pneumonia and are thus not liable to errors that can cause future antibiotic resistance (Graham et al, ; Puett et al, Puett, Sadler, et al, ). Since prescribing antibiotics is a critical component of CMAM, it is unknown if CHWs in SA will be granted the rights to administer them.…”
Section: Discussionmentioning
confidence: 99%
“…Even when antibiotics are available, a third of children may not complete the full course of treatment 5. This illustrates an additional issue in delivering effective treatment for childhood pneumonia: ensuring adherence to the treatment regimen.…”
Section: Introductionmentioning
confidence: 99%